2018
DOI: 10.1111/bcp.13726
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age and renal impairment on the steady state pharmacokinetics of filgotinib, a selective JAK1 inhibitor

Abstract: AimsFilgotinib (GS‐6034, formerly GLPG0634) is an oral, selective Janus kinase 1 (JAK1) inhibitor that showed early response and sustained efficacy in patients with rheumatoid arthritis and with Crohn's disease. The aim of the present study was to investigate the impact of age and renal impairment (RI) on the pharmacokinetics (PK) of filgotinib and its main metabolite.MethodsThe effect of age was assessed in two groups of 10 elderly healthy subjects (65–74 and ≥75 years of age) and a control group of 10 younge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 14 publications
0
30
0
1
Order By: Relevance
“…In einer experimentellen Studie konnte gezeigt werden, dass eine leicht bis moderat eingeschränkte Nierenfunktion (Stadium CKD G2, G3a und G3b) keinen Einfluss auf die Plasmakonzentration von Filgotinib aufweist. Bei Patienten mit einer chronischen Niereninsuffizienz im Stadium CKD G4 (eGFR 29-15 ml/min/1,73m²) kommt es durch die primäre renale Elimination von Filgotinib und sein Hauptmetabolit zu einem Anstieg der Plasmakonzentration [27].…”
Section: Targeted Synthetische Disease-modifying Antirheumatic Drugsunclassified
“…In einer experimentellen Studie konnte gezeigt werden, dass eine leicht bis moderat eingeschränkte Nierenfunktion (Stadium CKD G2, G3a und G3b) keinen Einfluss auf die Plasmakonzentration von Filgotinib aufweist. Bei Patienten mit einer chronischen Niereninsuffizienz im Stadium CKD G4 (eGFR 29-15 ml/min/1,73m²) kommt es durch die primäre renale Elimination von Filgotinib und sein Hauptmetabolit zu einem Anstieg der Plasmakonzentration [27].…”
Section: Targeted Synthetische Disease-modifying Antirheumatic Drugsunclassified
“…Hepatic impairment does not significantly impact the pharmacokinetics (PK) of filgotinib as it is primarily metabolized by carboxylesterase isoform 2, enzyme systems that are present in high levels throughout the body. 7,16 Moderate hepatic impairment had no clinically relevant impact on the C max of filgotinib or metabolite. 17 Mild to moderate renal impairment has not been shown to impact the C max of filgotinib.…”
mentioning
confidence: 95%
“…6 Filgotinib is primarily metabolized by carboxylesterase isoform 2, resulting in the loss of the cyclopropyl carboxylic acid group and formation of its major, circulating metabolite, which is predominantly excreted in the urine (>80%). 7,8 The metabolite also exhibits selective JAK1 inhibition, with approximately 16-to 20-fold higher exposure and longer half-life (23-27 hours for the metabolite versus 5-6 hours for filgotinib) but ß19-fold lower potency than filgotinib. 7,9,10 In phase 2 studies, filgotinib has shown clinical efficacy, rapid onset of activity, and a favorable safety and tolerability profile both as monotherapy and in combination with methotrexate in subjects with moderate to severe rheumatoid arthritis, [11][12][13] and in subjects with moderate to severe Crohn's disease.…”
mentioning
confidence: 99%
See 2 more Smart Citations